Thermal and electrical performance of uncooled, nature-cooled, and photovoltaic thermal module - Dwivedi, Pushpendu; Ganesh, Sujay Ashwinraj; Kumarasamy, Sudhakar; Soni, Archana; Priya, S. Shanmuga (Hindawi Limited, 2023)
The experimental study is aimed at analyzing photovoltaic module's thermal and electrical performance (PV) with back surface cooling under Malaysian tropical climate conditions. The performance of a passively cooled PV module integrated with biomaterial (moist coconut fiber) was compared with a photovoltaic thermal (PVT) system with water circulation at the rate of 0.02 kg s-1 and a reference PV module. The study observed that the passively cooled PV module succeeded in reducing the module surface temperature by more than 20%. However, the PVT system reduced the temperature only by less than 17%. The electrical energy efficiency was improved remarkably in the passively cooled PV module by almost 11%, but the PVT system managed to increase the electrical efficiency by 9%, approximately. It can be concluded that nature-inspired coconut fiber-based cooling can be one of the potential alternatives to active cooling methods.